Calculated-Experimental Model for Multilayer Shield - Al-Arif, Maan S.; Kakil, Diyaree O. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2015)
The effective linear attenuation coefficients and build-up factors for single shield of Al, Fe, Pb, and for multi-layer shield of Al-Pb, Al-Fe, Fe-Pb, Al-Fe-Pb as a function of shield thickness, atomic number, and order of the materials composing the shield are investigated for two photon energies of 0.662 MeV and 1.25 MeV. Two derived practical formulas to calculate the effective attenuation coefficient and build-up factor for multilayer shields are used. It is noticed that changing the order of the materials among the shield has no significant effect on the experimental result. Measurement agrees well with the trend of the suggested formulas for calculating the effective attenuation coefficient and the buildup factor. The linear attenuation coefficient is observed to have a strange dependency with the atomic number and photon energy. For single layer shield, the attenuation coefficient increases with decreasing atomic number at low photon energy and increasing with increasing atomic number at high photon energy.